Perceptions of nurse educators regarding the implementation of the occupational specific dispensation at a selected nursing college in Limpopo Province - M. D.N. Mcur; Fhumulani M. Mulaudzi (AOSIS, 2015)
The aim of this study was to explore and describe the perceptions of nurses regarding the implementation of the occupation-specific dispensation (OSD) in a selected nursing college in Limpopo province. A qualitative approach was used with a purposive sampling method for the selection of 12 voluntary participants who had worked for more than five years and been subjected to the implementation of OSD. In-depth interviews were conducted and data analysed according to Tesch's method. The perceptions of nurse educators were shared through participants' responses to a central research question. Participants expressed different responses, both positive and negative. The findings of this study demonstrated: high expectations, unfair treatment in relation to the implementation, and reactions to introduction of OSD. Participants also identified envisaged ways of improving the situation through the identification of ways to correct the problems. This study recommended that management ensure that nurse educators' remuneration packages are competitive with those of similar professions in the clinical setting. Recognition of nurse educators' additional qualifications, long-service experiences and rural allowance reviews in nursing education should be taken into consideration urgently.